2011
DOI: 10.1016/j.jcat.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy, microscopy and theoretical study of NO adsorption on MoS2 and Co–Mo–S hydrotreating catalysts

Abstract: Infrared (IR) spectroscopy using NO as a probe molecule has been one of the important methods for characterizing hydrotreating catalysts, since this technique provides information on the nature and quantity of active edge sites of these catalysts. However, due to the strong adsorption of NO, which may lead to significant edge reconstructions, it has not been clear, how the characteristics of the adsorption complexes may reflect the nature of the original edge sites. By combining IR spectroscopy measurements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 100 publications
0
20
0
Order By: Relevance
“…Topsøe, B. Clausen, S. Helveg, and others at Haldor Topsøe A/S, we have, in the last decade, published a series of studies where scanning tunneling microscopy (STM) was applied as the principal technique to study the adsorption effects relevant to HDS reactions on MoS 2 nanoparticles and we have provided the hitherto most detailed atomic-level experimental view on molecular interactions on the active MoS 2 and CoMoS nanoparticles [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Topsøe, B. Clausen, S. Helveg, and others at Haldor Topsøe A/S, we have, in the last decade, published a series of studies where scanning tunneling microscopy (STM) was applied as the principal technique to study the adsorption effects relevant to HDS reactions on MoS 2 nanoparticles and we have provided the hitherto most detailed atomic-level experimental view on molecular interactions on the active MoS 2 and CoMoS nanoparticles [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Among disulphides, MoS 2 is interesting both as a hydro-treating and as a desulphurisation catalyst. The complicated chemistry of its edge surfaces has stimulated several theoretical and experimental investigations [177][178][179][180][181][182]. More systematic studies involving a broader range of metal sulphides [183] are also reported.…”
Section: The Surface Of Transition Metal Sulphides: Bulk and Nanocrysmentioning
confidence: 99%
“…The catalytic active phase termed CoMoS (or NiMoS for Ni-promoted MoS 2 ) is MoS 2 nanoparticles with the edges decorated by Co [33]. The exact location and local environment of Co have been determined by a combination of EXAFS, IR, DFT, STM, and TEM studies [34][35][36][37][38]. The close agreement between experimental observations and thermodynamics based on DFT gives confidence of DFT's ability to predict the structure and energetics of these rather complicated structures [35,37,[39][40][41].…”
Section: Beyond Transition Metal-based Catalysismentioning
confidence: 99%